(untitled) (Research, Society and Development, 2021)
This study had the objective to evaluate the effect of irrigation and fertigation (NK) in the hydraulic conductivity and diffusivity of an Oxisol cultivated with sugarcane. The experimental design comprised randomized blocks in a 5 × 2 factorial scheme, with four replications. Treatments consisted of five levels of water replacement (100, 75, 50, 25 and 0%), with and without fertirrigation (NK). The planting of sugarcane, cultivar RB85-5453, was performed in a double row (W-shaped), 8 m long, with 1.80 m spacing between the double rows, the distance between the crops in the double row was 0.40 m, with a total area of 52,8 m2 in each paddock. For treatments with water, replacement (WR) a drip tube was placed in the ground at a depth of 0.20 m among the furrows of the double row. The drip tube (DRIPNET PC 16150) comprised a thin wall, 1.0 bar pressure, nominal discharge 1.0 L h-1, and 0.50 m spacing between drippers. Nitrogen was applied by fertirrigation at a dose of 100 Kg ha-1, at 30-day intervals, with 10 applications throughout the development of the sugarcane culture. Potassium fertilization was done partially, in 30% of the furrows, and the remaining part was treated with the irrigation water. Nitrogen and potassium were spread only in the treatment with 0% water replacement. Was evaluated hydraulic conductivity and diffusivity versus logarithmic pressure head, at a depth of 10 cm, using RETC software. The hydraulic diffusivity for water replacement of 25 and 50% with fertigation was 160.3 and 14.9 cm2 days-1 for the lower values of the logarithm of the pressure head.